Botulinum A toxin as a treatment of detrusor- sphincter dyssynergia in patients with spinal cord injury: MRI controlled transperineal injections. Issue 4 (1st October 1997) - Schurch, Brigitte; Hodler, Juerg; Rodic, Bilijana
Abstract : OBJECTIVES: To correlate clinical and urodynamic findings with MRI in patients with spinal cord injury and detrusor-sphincter dyssynergia who were consecutively treated with transperineal injections of botulinum-A toxin (BTX-A) under EMG control. METHODS: Six patients with spinal cord injury and upper motor neuron bladder dysfunction associated with detrusor- sphincter dyssynergia were prospectively analysed. One hundred international units (IU) BTX-A (Botox® in 1 ml normal saline without preservative) diluted 1 to 1 with 1 ml gadopentetate were injected transperineally under EMG control. MRI was started immediately after needle withdrawal. RESULTS: In all six patients gadopentetate was located in the external urethral sphincter on MRI. In no patient did traces of gadopentetate appear in the perineal musculature located in the vicinity of the external urethral sphincter. No patient developed resistance to BTX-A. All patients showed an (ongoing) improvement of their voiding function after BTX-A injections. CONCLUSIONS: Transperineal injections of BTX-A under EMG control are efficient in the release or amelioration of lower urinary tract obstruction due to detrusor sphincter dyssynergia in patients with spinal cord injury. Despite well described methods, EMG of the external urethral sphincter is difficult and it is not possible to definitively exclude false recordings of the surrounding perineal musculature. By the use of MRI it was shown that both the EMG recordings and transperineal injection method are precise.